Вы находитесь на странице: 1из 5

Perpendicular axis theorem

From Wikipedia, the free encyclopedia


In physics, the perpendicular axis theorem (or plane figure theorem) can be used
to determine the moment of inertia of a rigid object that lies entirely within
a plane, about an axis perpendicular to the plane, given the moments of inertia
of the object about two perpendicular axes lying within the plane. The axes must
all pass through a single point in the plane.
Define perpendicular axes {\displaystyle x\,} x\,, {\displaystyle y\,} y\,, and
{\displaystyle z\,} z\, (which meet at origin {\displaystyle O\,} O\,) so that t
he body lies in the {\displaystyle xy\,} xy\, plane, and the {\displaystyle z\,}
z\, axis is perpendicular to the plane of the body. Let Ix, Iy and Iz be moment
s of inertia about axis x, y, z respectively, the perpendicular axis theorem sta
tes that[1]
{\displaystyle I_{z}=I_{x}+I_{y}\,} I_z = I_x + I_y\,
This rule can be applied with the parallel axis theorem and the stretch rule to
find moments of inertia for a variety of shapes.
If a planar object (or prism, by the stretch rule) has rotational symmetry such
that {\displaystyle I_{x}\,} I_x\, and {\displaystyle I_{y}\,} I_y\, are equal,
then the perpendicular axes theorem provides the useful relationship:
{\displaystyle I_{z}=2I_{x}=2I_{y}\,} I_z = 2I_x = 2I_y\,
Derivation[edit]
Working in Cartesian co-ordinates, the moment of inertia of the planar body abou
t the {\displaystyle z\,} z\, axis is given by:[2]
{\displaystyle I_{z}=\int \left(x^{2}+y^{2}\right)\,dm=\int x^{2}\,dm+\int y^{2}
\,dm=I_{y}+I_{x}} I_{z} = \int \left(x^2 + y^2\right)\, dm = \int x^2\,dm + \int
y^2\,dm = I_{y} + I_{x}
On the plane, {\displaystyle z=0\,} z=0\,, so these two terms are the moments of
inertia about the {\displaystyle x\,} x\, and {\displaystyle y\,} y\, axes resp
ectively, giving the perpendicular axis theorem. The converse of this theorem is
also derived similarly.
Note that {\displaystyle \int x^{2}\,dm=I_{y}\neq I_{x}} \int x^2\,dm = I_{y} \
ne I_{x} because in {\displaystyle \int r^{2}\,dm} \int r^2\,dm , r measures t
he distance from the axis of rotation, so for a y-axis rotation, deviation dista
nce from the axis of rotation of a point is equal to its x co-ordinate.
Mass moment of inertia[edit]
The mass moment of inertia of a body around an axis can be determined from the m
ass moment of inertia around a parallel axis through the center of gravity.
Suppose a body of mass m is made to rotate about an axis z passing through the b
ody's center of gravity. The body has a moment of inertia Icm with respect to th
is axis. The parallel axis theorem states that if the body is made to rotate ins
tead about a new axis z' which is parallel to the first axis and displaced from
it by a distance d, then the moment of inertia I with respect to the new axis is
related to Icm by
{\displaystyle I=I_{\mathrm {cm} }+md^{2}.} I=I_{\mathrm {cm} }+md^{2}.
Explicitly, d is the perpendicular distance between the axes z and z'.
The parallel axis theorem can be applied with the stretch rule and perpendicular
axis theorem to find moments of inertia for a variety of shapes.
Parallel axes rule for area moment of inertia

Derivation[edit]
We may assume, without loss of generality, that in a Cartesian coordinate system
the perpendicular distance between the axes lies along the x-axis and that the
center of gravity lies at the origin. The moment of inertia relative to the z-ax
is is
{\displaystyle I_{\mathrm {cm} }=\int (x^{2}+y^{2})\,dm.} I_{\mathrm {cm} }=\int
(x^{2}+y^{2})\,dm.
The moment of inertia relative to the axis z', which is a perpendicular distance
d along the x-axis from the center of mass, is
{\displaystyle I=\int \left[(x+d)^{2}+y^{2}\right]\,dm} {\displaystyle I=\int \l
eft[(x+d)^{2}+y^{2}\right]\,dm}
Expanding the brackets yields
{\displaystyle I=\int (x^{2}+y^{2})\,dm+d^{2}\int dm+2d\int x\,dm.} {\displaysty
le I=\int (x^{2}+y^{2})\,dm+d^{2}\int dm+2d\int x\,dm.}
The first term is Icm and the second term becomes md2. The integral in the final
term is the x-coordinate of the center of mass, which is zero by construction.
So, the equation becomes:
{\displaystyle I=I_{\mathrm {cm} }+md^{2}.} I=I_{\mathrm {cm} }+md^{2}.
Tensor generalization[edit]
The parallel axis theorem can be generalized to calculations involving the inert
ia tensor. Let Iij denote the inertia tensor of a body as calculated at the cent
er of mass. Then the inertia tensor Jij as calculated relative to a new point is
{\displaystyle J_{ij}=I_{ij}+m\left(|\mathbf {R} |^{2}\delta _{ij}-R_{i}R_{j}\ri
ght),} J_{ij}=I_{ij}+m\left(|\mathbf {R} |^{2}\delta _{ij}-R_{i}R_{j}\right),
where {\displaystyle \mathbf {R} =R_{1}\mathbf {\hat {x}} +R_{2}\mathbf {\hat {y
}} +R_{3}\mathbf {\hat {z}} \!} \mathbf {R} =R_{1}\mathbf {\hat {x}} +R_{2}\math
bf {\hat {y}} +R_{3}\mathbf {\hat {z}} \! is the displacement vector from the ce
nter of mass to the new point, and dij is the Kronecker delta.
For diagonal elements (when i = j), displacements perpendicular to the axis of r
otation results in the above simplified version of the parallel axis theorem.
The generalized version of the parallel axis theorem can be expressed in the for
m of coordinate-free notation as
{\displaystyle \mathbf {J} =\mathbf {I} +m\left[\left(\mathbf {R} \cdot \mathbf
{R} \right)\mathbf {E} _{3}-\mathbf {R} \otimes \mathbf {R} \right],} \mathbf {J
} =\mathbf {I} +m\left[\left(\mathbf {R} \cdot \mathbf {R} \right)\mathbf {E} _{
3}-\mathbf {R} \otimes \mathbf {R} \right],
where E3 is the 3??3 identity matrix and {\displaystyle \otimes } \otimes is the
outer product.
Area moment of inertia[edit]
The parallel axes rule also applies to the second moment of area (area moment of
inertia) for a plane region D:
{\displaystyle I_{z}=I_{x}+Ar^{2},} I_{z}=I_{x}+Ar^{2},
where Iz is the area moment of inertia of D relative to the parallel axis, Ix is
the area moment of inertia of D relative to its centroid, A is the area of the
plane region D, and r is the distance from the new axis z to the centroid of the
plane region D. The centroid of D coincides with the centre of gravity of a phy
sical plate with the same shape that has uniform density.
Polar moment of inertia for planar dynamics[edit]

Polar moment of inertia of a body around a point can be determined from its pola
r moment of inertia around the center of mass.
The mass properties of a rigid body that is constrained to move parallel to a pl
ane are defined by its center of mass R = (x, y) in this plane, and its polar mo
ment of inertia IR around an axis through R that is perpendicular to the plane.
The parallel axis theorem provides a convenient relationship between the moment
of inertia IS around an arbitrary point S and the moment of inertia IR about the
center of mass R.
Recall that the center of mass R has the property
{\displaystyle \int _{V}\rho (\mathbf {r} )(\mathbf {r} -\mathbf {R} )\,dV=0,} \
int _{V}\rho (\mathbf {r} )(\mathbf {r} -\mathbf {R} )\,dV=0,
where r is integrated over the volume V of the body. The polar moment of inertia
of a body undergoing planar movement can be computed relative to any reference
point S,
{\displaystyle I_{S}=\int _{V}\rho (\mathbf {r} )(\mathbf {r} -\mathbf {S} )\cdo
t (\mathbf {r} -\mathbf {S} )\,dV,} I_{S}=\int _{V}\rho (\mathbf {r} )(\mathbf {
r} -\mathbf {S} )\cdot (\mathbf {r} -\mathbf {S} )\,dV,
where S is constant and r is integrated over the volume V.
In order to obtain the moment of inertia IS in terms of the moment of inertia IR
, introduce the vector d from S to the center of mass R,
{\displaystyle {\begin{aligned}I_{S}&=\int _{V}\rho (\mathbf {r} )(\mathbf {r} \mathbf {R} +\mathbf {d} )\cdot (\mathbf {r} -\mathbf {R} +\mathbf {d} )\,dV\\&=
\int _{V}\rho (\mathbf {r} )(\mathbf {r} -\mathbf {R} )\cdot (\mathbf {r} -\math
bf {R} )dV+2\mathbf {d} \cdot \left(\int _{V}\rho (\mathbf {r} )(\mathbf {r} -\m
athbf {R} )\,dV\right)+\left(\int _{V}\rho (\mathbf {r} )\,dV\right)\mathbf {d}
\cdot \mathbf {d} .\end{aligned}}} {\begin{aligned}I_{S}&=\int _{V}\rho (\mathbf
{r} )(\mathbf {r} -\mathbf {R} +\mathbf {d} )\cdot (\mathbf {r} -\mathbf {R} +\
mathbf {d} )\,dV\\&=\int _{V}\rho (\mathbf {r} )(\mathbf {r} -\mathbf {R} )\cdot
(\mathbf {r} -\mathbf {R} )dV+2\mathbf {d} \cdot \left(\int _{V}\rho (\mathbf {
r} )(\mathbf {r} -\mathbf {R} )\,dV\right)+\left(\int _{V}\rho (\mathbf {r} )\,d
V\right)\mathbf {d} \cdot \mathbf {d} .\end{aligned}}
The first term is the moment of inertia IR, the second term is zero by definitio
n of the center of mass, and the last term is the total mass of the body times t
he square magnitude of the vector d. Thus,
{\displaystyle I_{S}=I_{R}+Md^{2},\,} I_{S}=I_{R}+Md^{2},\,
which is known as the parallel axis theorem.[2]
Moment of inertia matrix[edit]
The inertia matrix of a rigid system of particles depends on the choice of the r
eference point. There is a useful relationship between the inertia matrix relati
ve to the center of mass R and the inertia matrix relative to another point S. T
his relationship is called the parallel axis theorem.
Consider the inertia matrix [IS] obtained for a rigid system of particles measur
ed relative to a reference point S, given by
{\displaystyle [I_{S}]=-\sum _{i=1}^{n}m_{i}[r_{i}-S][r_{i}-S],} [I_{S}]=-\sum _
{i=1}^{n}m_{i}[r_{i}-S][r_{i}-S],
where ri defines the position of particle Pi, i = 1, ..., n. Recall that [ri - S
] is the skew-symmetric matrix that performs the cross product,
{\displaystyle [r_{i}-S]\mathbf {y} =(\mathbf {r} _{i}-\mathbf {S} )\times \math
bf {y} ,} [r_{i}-S]\mathbf {y} =(\mathbf {r} _{i}-\mathbf {S} )\times \mathbf {y
} ,

for an arbitrary vector y.


Let R be the center of mass of the rigid system, then
{\displaystyle \mathbf {R} =(\mathbf {R} -\mathbf {S} )+\mathbf {S} =\mathbf {d}
+\mathbf {S} ,} \mathbf {R} =(\mathbf {R} -\mathbf {S} )+\mathbf {S} =\mathbf {
d} +\mathbf {S} ,
where d is the vector from the reference point S to the center of mass R. Use th
is equation to compute the inertia matrix,
{\displaystyle [I_{S}]=-\sum _{i=1}^{n}m_{i}[r_{i}-R+d][r_{i}-R+d].} [I_{S}]=-\s
um _{i=1}^{n}m_{i}[r_{i}-R+d][r_{i}-R+d].
Expand this equation to obtain
{\displaystyle [I_{S}]=\left(-\sum _{i=1}^{n}m_{i}[r_{i}-R][r_{i}-R]\right)+\lef
t(-\sum _{i=1}^{n}m_{i}[r_{i}-R]\right)[d]+[d]\left(-\sum _{i=1}^{n}m_{i}[r_{i}R]\right)+\left(-\sum _{i=1}^{n}m_{i}\right)[d][d].} [I_{S}]=\left(-\sum _{i=1}^
{n}m_{i}[r_{i}-R][r_{i}-R]\right)+\left(-\sum _{i=1}^{n}m_{i}[r_{i}-R]\right)[d]
+[d]\left(-\sum _{i=1}^{n}m_{i}[r_{i}-R]\right)+\left(-\sum _{i=1}^{n}m_{i}\righ
t)[d][d].
The first term is the inertia matrix [IR] relative to the center of mass. The se
cond and third terms are zero by definition of the center of mass R,
{\displaystyle \sum _{i=1}^{n}m_{i}(\mathbf {r} _{i}-\mathbf {R} )=0.} \sum _{i=
1}^{n}m_{i}(\mathbf {r} _{i}-\mathbf {R} )=0.
And the last term is the total mass of the system multiplied by the square of th
e skew-symmetric matrix [d] constructed from d.
The result is the parallel axis theorem,
{\displaystyle [I_{S}]=[I_{R}]-M[d]^{2},} [I_{S}]=[I_{R}]-M[d]^{2},
where d is the vector from the reference point S to the center of mass R.[3]
Identities for a skew-symmetric matrix[edit]
In order to compare formulations of the parallel axis theorem using skew-symmetr
ic matrices and the tensor formulation, the following identities are useful.
Let [R] be the skew symmetric matrix associated with the position vector R = (x,
y, z), then the product in the inertia matrix becomes
{\displaystyle -[R][R]=-{\begin{bmatrix}0&-z&y\\z&0&-x\\-y&x&0\end{bmatrix}}^{2}
={\begin{bmatrix}y^{2}+z^{2}&-xy&-xz\\-yx&x^{2}+z^{2}&-yz\\-zx&-zy&x^{2}+y^{2}\e
nd{bmatrix}}.} -[R][R]=-{\begin{bmatrix}0&-z&y\\z&0&-x\\-y&x&0\end{bmatrix}}^{2}
={\begin{bmatrix}y^{2}+z^{2}&-xy&-xz\\-yx&x^{2}+z^{2}&-yz\\-zx&-zy&x^{2}+y^{2}\e
nd{bmatrix}}.
This product can be computed using the matrix formed by the outer product [R RT]
using the identify
{\displaystyle -[R]^{2}=|\mathbf {R} |^{2}[E_{3}]-[\mathbf {R} \mathbf {R} ^{T}]
={\begin{bmatrix}x^{2}+y^{2}+z^{2}&0&0\\0&x^{2}+y^{2}+z^{2}&0\\0&0&x^{2}+y^{2}+z
^{2}\end{bmatrix}}-{\begin{bmatrix}x^{2}&xy&xz\\yx&y^{2}&yz\\zx&zy&z^{2}\end{bma
trix}},} -[R]^{2}=|\mathbf {R} |^{2}[E_{3}]-[\mathbf {R} \mathbf {R} ^{T}]={\beg
in{bmatrix}x^{2}+y^{2}+z^{2}&0&0\\0&x^{2}+y^{2}+z^{2}&0\\0&0&x^{2}+y^{2}+z^{2}\e
nd{bmatrix}}-{\begin{bmatrix}x^{2}&xy&xz\\yx&y^{2}&yz\\zx&zy&z^{2}\end{bmatrix}}
,
where [E3] is the 3 3 identity matrix.
Also notice, that
{\displaystyle |\mathbf {R} |^{2}=\mathbf {R} \cdot \mathbf {R} =\operatorname {

tr} [\mathbf {R} \mathbf {R} ^{T}],} |\mathbf {R} |^{2}=\mathbf {R} \cdot \mathb
f {R} =\operatorname {tr} [\mathbf {R} \mathbf {R} ^{T}],
where tr denotes the sum of the diagonal elements of the outer product matrix, k
nown as its trace.